2004
DOI: 10.1007/s00018-004-4029-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the yeast tricalbins: membrane-bound multi-C2-domain proteins that form complexes involved in membrane trafficking

Abstract: In a survey of yeast genomic sequences encoding calcium- and phospholipid-binding C2 domains, three homologous genes were identified that encode proteins that each have three C2 domains and an apparent transmembrane domain near the N terminus. The name tricalbins is suggested for these proteins, corresponding to the open reading frames YOR086c (TCB1), YNL087w (TCB2), and YML072c (TCB3). An antiserum was raised against the C-terminal portion of tricalbin 2 and used on Western blots to demonstrate that the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 54 publications
5
23
0
Order By: Relevance
“…However, the present study would not have revealed subtle changes in mouse tissue structure, physiology or behavior. This said, despite the greatly increased complexity of the mouse system, our findings are in fact in line with data on the inactivation of the Tcbs of yeast 11,12 . ER-PM junctions in yeast were only significantly affected when all 6 ER-PM tethering proteins (Ist2, Scs2 and 22, and Tcbs 1, 2 and 3) were inactivated, and even then the growth rate in rich medium remained unaffected 12 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the present study would not have revealed subtle changes in mouse tissue structure, physiology or behavior. This said, despite the greatly increased complexity of the mouse system, our findings are in fact in line with data on the inactivation of the Tcbs of yeast 11,12 . ER-PM junctions in yeast were only significantly affected when all 6 ER-PM tethering proteins (Ist2, Scs2 and 22, and Tcbs 1, 2 and 3) were inactivated, and even then the growth rate in rich medium remained unaffected 12 .…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, they were shown to enhance the formation of contact sites between the endoplasmic reticulum (ER) and the plasma membrane (PM) in response to Ca 2+ signaling, 6,7 see 8 , 9 and 10 for reviews. The E-Syts are broadly conserved throughout the animal kingdom and are analogous to the tricalbins (Tcb1, 2 and 3), which perform analogous functions in ER-PM tethering and phospholipid transport in yeast 11,12 . By their ability to form ER-PM junctions, the E-Syts were shown to facilitate the transport of phospholipids to the plasma membrane (PM) 7,13-15 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Deletion studies in yeast of the Tricalbin family show that they are highly functionally redundant and in concert with other membrane tethering proteins they promote ER-PM junction formation. 13,20,21 Indeed, deletion of all 3 Tcbs was not in itself sufficient to eliminate ER-PM tethering and this required deletion of 3 other proteins, Ist2 (a TMEM16 ion channel family member) and the vesicle-associated membrane protein-associated protein (VAP) orthologs Scs2 and Scs22. We previously demonstrated a requirement for Xenopus Esyt2 in FGF signal transduction, receptor …”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the tricalbin ("tri" for three, "ca" for calcium, "l" for lipid, and "bin" for binding) (33) protein Tcb2p or Tcb3p were found in all evolved strains with maximum fitness scores (Fig. 1).…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, limonene resistance may also be due to the loss of the tricalbin complex. Tcb2p forms a heterocomplex with Tcb3p (and Tcb1p) by binding to the C-terminal portions of tricalbins 1 and 3 (33). With the C terminus of Tcb3p absent in both truncated versions (ending at position 989 or 531), we questioned if limonene resistance was associated with the breakdown of the Tcb2p-Tcb3p tricalbin complex.…”
Section: Fig 1 Summary Of the Relative Fitness And Genetic Mutations mentioning
confidence: 99%